Spatial patterns and inequity of urban green space supply in China - Yiyi Huang (Elsevier, 2021)
Urban green space (UGS) is essential to the improvement of human well-being and health, and the inequity of UGS supply has received widespread concern. The urban green space availability (UGSA) can effectively evaluate UGS supply. However, the UGSA under different daily transportation patterns has not received enough attention, as well as the potential of UGS that is not available by transportation patterns. Meanwhile, the inequity of UGS supply between cities with different economic development levels at the regional or national scale is still unclear. So, we constructed seven UGS indicators to represent the UGS supply: UGSA considering four kinds of daily transportation patterns (UGSA0.5 km, UGSA2.5 km, UGSA10km, and UGSA30km), the potential of UGS (PUGS), the proportion of PUGS (PPUGS), and stock of UGS indicator (SUGS). The spatial patterns of availability, potential, and stock of UGS in 366 cities on the Chinese mainland in 2015 were captured. Then, the concentration curve and concentration index (CI) were applied to describe the inequity of UGS supply between the cities. Finally, we used correlation analysis, regression analysis, and GeoDetector techniques to explore the driving factors of the spatial pattern of availability and potential of UGS. The results showed that: (1) The SUGS, PUGS, and PPUGS were lower in the southeastern region indicated by the Hu Huanyong Line than that in the northwestern region. Only 44.11% of China's UGS were available through the daily transportation patterns. The spatial patterns of the four UGSA were similar, while the UGSA30km’s hot spots appeared in Southwest China. (2) Less developed cities occupied more SUGS, PUGS, and PPUGS. With the increase of buffer radius, the equity of UGSA among cities was gradually improved, while developed cities always possessed more UGSA. (3) With the increase of buffer radius, the dominant driving factors of UGSA indicators gradually changed from social economy and infrastructure variables to physical geography variables. Our study provides new evidence for a comprehensive understanding of UGSA, and the results of UGS supply and its inequity will contribute to sustainable UGS development in targeting cities or regions in China.